Dynamic cobweb models with conformable fractional derivatives. (May 2019) - Bohner, Martin; Hatipoğlu, Veysel Fuat
Abstract: In this paper, basic and more realistic dynamic cobweb models are developed in terms of conformable fractional derivatives. The general solutions and stability criteria for the proposed models are given. Moreover, the developed models are illustrated with examples on several time scales.